Relatório de estágio técnico profissional supervisionado em medicina veterinária: clínica médica de pequenos animais - Santos, Maria Ester dos (2023)
The Professional Technical Internship (ETP) aims to provide practical experience during the period internship, combining the knowledge acquired during graduation and allowing complement the training of Veterinary Medicine students. The ETP was carried out in the area of Small Animal Medical Clinic, at the Veterinary Hospital of the University of Passo Fund (HV-UPF), with the academic guidance of Prof. Dr. Renan Idalencio and the supervision of Veterinary Doctor Gissele de Quadros Krahl, from July 24th to October 24th, totaling 483 hours. Through ETP it was possible to experience the clinical routine within a teaching hospital, providing support for various clinical services, imaging exams, laboratory, outpatient and emergency procedures, in addition to monitoring and care with hospitalized patients. This report describes the internship location, the activities developed and the conditions monitored during this period. For better understanding, the information will be presented in table format. Finally, a case of canine monocytic ehrlichiosis, in a canine, German Spitz, female, presenting thrombocytopenia.